"An Pag-ino han gin-agian nga dalan han pagbag-o" examining the implementation of a community-based drug rehabilitation program - Espejo, Jonas S.; Espina, Ervina A.; Gaspang, Elkanah G.; Manansala, Patrick Jubiemn G. (2023)
The community-based drug rehabilitation (CBDR) program was designed to tackle the drug use of the people who used drugs (PWUDs) and lead the shift in approach towards drug use from criminalization to a public health viewpoint. The purpose of this study was to examine the perceptions and sentiments of the individuals actively involved in the implementation of the CBDR program in Tolosa, Leyte, Philippines through Bronfenbrenner's (1979) ecological systems theory. A descriptive phenomenological design was utilized, and data analysis was conducted through thematic analysis (Braun & Clarke, 2006). The study analyzed the interview responses of six (6) BHW volunteers, two (2) MSWDO coordinators, and two (2) USAID program coordinators. The data gathered were categorized into two main themes, (1) the local components and processes that affected CBDR implementation, and (2) the program implementers insights on the pilot implementation of CSDR program. Overall results of this study identified lapses in the implementation of the program. However, results also indicated that program implementers considered the pilot implementation in Tolosa as successful regardless of the lapses they have identified. Provided the results, future CBDR programs should utilize the data gathered in Tolosa to avoid possible lapses in their implementation. Future studies should also study the insights of other sectors and agencies involved in the implementation of the program.
Undergraduate thesis (B.A. Psychology) -- University of the Philippines, Tacloban.